A novel approach toward colon cancer treatment involving mucoadhesion and tumour-targeting of curcumin-containing nanoparticles - Sabra, Rayan (2019)
Curcumin is a natural, lipid-soluble compound extracted from turmeric with no perceptible toxicity. Recent studies have shown that curcumin has distinctive anticancer properties against colorectal cancer (CRC). However, oral administration of curcumin results in low absorption, rapid metabolism and elimination, and limited systemic bioavailability. To surmount these limitations, nano-encapsulation technology may be applied. Various polymers have been utilised to fabricate the encapsulant in nanoparticles, yet those of natural origin are more favoured since they are biocompatible, biodegradable and cause no toxicity. Thus, encapsulating curcumin in natural polymeric nanoparticles that offer opportunities for targeted delivery, are a promising means for improving treatment of CRC through increased local drug concentration and minimising side effects on surrounding healthy cells in the colon. Moreover, incorporating targeting ligands on the nanoparticles introduces cell specificity through receptor-specific binding and tissue uptake, enabling curcumin to reach intracellular targets. This thesis describes the development of curcumin-containing cetuximab-modified citrus pectin-chitosan nanoparticles for the aim of delivering curcumin to colon cancer tissue when administered orally.